Remembering Professor Emeritus Lady Dr. Putipannee Vorakitpokatorn: A visionary anesthesiologist and ICU pioneer: Remembering Professor Putipannee - Sodapak, Chaianan (Clinical Critical Care, 2025)
We mourn the loss of Lady Dr. Putipannee Vorakitpokatorn or “Ajahn Tam”, beloved wife, mother, teacher, a remarkable anesthesiologist, critical care physician, and a mentor who dedicated her life to improve patient care in Thailand Ajahn Tam passed away peacefully on October 11st, 2023, her unwavering passion and compassion touched the lives of countless individuals.